DIPG-27. TARGETING FACILITATES CHROMATIN TRANSCRIPTION (FACT) AS A NOVEL STRATEGY FOR DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) THAT ENHANCES RESPONSE TO HISTONE DEACETYLASE (HDAC) INHIBITION. (4th December 2020) - Ehteda, Anahid; Franshaw, Laura; Liu, Jie; Joshi, Swapna; Simon, Sandy; Pang, Chi Nam Ignatius; Giorgi, Federico; Pandher, Ruby; Ung, Caitlin; Tolhurst, Ornella; Mayoh, Chelsea; Khan, Aaminah; et al.
Abstract: Diffuse intrinsic pontine glioma (DIPG) is an aggressive and incurable childhood brain tumour for which new treatments are needed. A high throughput drug screen of 3500 pharmaceutical compounds identified anti-malarials, including quinacrine as having potent activity against DIPG neurospheres. CBL0137, a compound modelled on quinacrine, is an anti-cancer compound which targets Facilitates Chromatin Transcription (FACT), a chromatin remodelling complex involved in transcription, replication, and DNA repair. CBL0137 effectively crosses the blood-brain barrier and is currently in Phase I trials in adult cancer. CBL0137 induced apoptosis in DIPG neurospheres in vitro and had profound cytotoxic activity against a panel of DIPG cultures. In a DIPG orthotopic model, treatment with CBL0137 significantly improved survival. We found that treatment with CBL0137 up-regulated TP53 and increased histone H3.3 acetylation and tri-methylation in DIPG cells. We therefore examined the interaction between CBL0137 and the HDAC inhibitor, panobinostat. In vitro experiments showed that the two agents had profound synergistic activity against DIPG neurospheres in clonogenic assays and enhanced apoptosis. Transcriptomic analysis and immunoblotting indicated that combination treatment activated signalling pathways controlled by Retinoblastoma (RB)/E2F1 and subsequently increased phosphorylation and enzymatic activity of enhancer of zeste homolog 2 (EZH2). Consistent with the in vitro results, the combination of CBL0137 and panobinostat significantly prolonged the survival of two orthotopic models of DIPG, while histological analysis showed increased H3K27me3 and decreased Ki67 positive cells. Given these promising results, a paediatric trial of CBL0137 is planned to open through the Children's Oncology Group with an expansion cohort for DIPG patients.